Impact of Middle Pleistocene (Saalian) glacial lake-outburst floods on the meltwater-drainage pathways in northern central Europe: Insights from 2D numerical flood simulation - Lang J; Alho P; Kasvi E; Goseberg N; Winsemann J (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The terrestrial margins of the Middle Pleistocene ice sheets in northern central Europe were characterised by the formation of extensive ice-dammed lakes, which were controlled by the blockage of spillways by the ice margin. The largest ice-dammed lake had a volume of similar to 224 km(3) and formed in a late stage of the first Saalian ice advance (MIS 6) in central Germany. The failure of the ice dam in the bedrock-outlet channel triggered a major glacial lake-outburst flood. Flood-related erosional and depositional features include large-scale scours, trench-like channels, streamlined hills, giant bars and run-up deposits, indicating a wide spreading of the outburst flood in an early stage and the incision of trench-like valleys in a later stage. The incision of large valleys in the proximal flood pathway strongly impacted the regional drainage system by providing an efficient drainage network. The trench-like channels initiated by the lake-outburst flood became a crucial part of the ice-marginal drainage and subsequent fluvial system.The reconstructed outlet hydrographs imply peak discharges of 465,000-673,000 m(3)s(-1). The numerical simulation indicates flow depths of up to 87 m, flow velocities of up to 7 ms(-1), peaks of the bed shear stress of 2500 Nm(-2) and the inundation of large parts of northwestern Germany and the northern Netherlands. The numerical simulation of the outburst flood was conducted on both the modem digital elevation model and on palaeotopographic models, representing the palaeotopography prior to the outburst flood and during maximum flood-related incision, respectively.Distally, the outburst flood probably followed an east-west trending route through northwestern Germany and the central Netherlands into the ice-dammed lake in the southern North Sea Basin. The added water volume might have led to the overspill and drainage of the proglacial lakes in the central Netherlands and the North Sea Lake in a chain reaction, eventually opening an east-west trending meltwater-drainage pathway along the southwestern margin of the decaying ice sheet. (C) 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).